Solution-processed SiO2 gate insulator formed at low temperature for zinc oxide thin-film transistors1. Issue 45 (20th May 2015) - Jeong, Yesul; Pearson, Christopher; Kim, Hyun-Gwan; Park, Man-Young; Kim, Hongdoo; Do, Lee-Mi; Petty, Michael C.
<x xml:space="preserve">Abstract</x> A ZnO transistor with carrier mobility of 3 cm2 V−1 s−1 using a SiO2 insulator formed at low-temperature (180 °C) from solution-processed perhydropolysilazane.